PHYSICO-CHEMICAL PARAMETERS, PLANKTON, MACROZOOBENTHOS AND FISH FAUNA OF IBUYA RIVER, SEPETERI, SOUTH-WESTERN NIGERIA (2016)
Ibuya River runs across the Old Oyo National Park, a wildlife and recreational park. There is paucity of information on the limnology of the river which will provide information on the ecological status relevant for sustainable management. Therefore, this study was carried out to investigate the physico-chemical parameters, diversity and abundance of plankton, macrozoobenthos and fish fauna of Ibuya River. Surface water (72), plankton (72) and macrozoobenthic (72) samples were collected monthly from September 2012 to February 2014 at randomly selected stations (i-iv) along the river. Water temperature, pH and Dissolved Oxygen (DO) were measured in situ, while hardness, turbidity, phosphate (PO₄3˗), sulphate (SO₄2-), heavy metals including cadmium (Cd), Iron (Fe) and lead (Pb), were determined in the laboratory according to APHA method. Plankton samples were collected with plankton net (mesh size, 55 µm), identified and counted microscopically. Macrozoobenthos were collected with Van-Veen grab (0.086 m2), identified and counted macroscopically. Fish samples were collected with gill net (mesh size 45 mm), identified and counted. All identifications including pollution indicator species were done using standard identification keys. Species diversity was determined with Shannon-Wiener index HI. Descriptive statistics, student t-test, one-way ANOVA, Pearson correlation coefficient and Principal Component Analysis (PCA) were used for analysis of data at α0.05. Water temperature was 24.8±0.2 °C; pH, 7.60±0.04; DO, 4.4±0.2 mg/L; hardness, 39.6±2.1 mg/L CaCO3; turbidity, 19.4±0.9 FTU; Cd, 0.2±0.1 mg/L; Pb, 0.7±0.1 mg/L; Fe, 2.1±0.2 mg/L; PO₄3˗, 24.3±2.8 mg/L; and SO₄2-, 31.8±3.1 mg/L. Turbidity had significant spatial and seasonal variation at p<0.001 while pH and SO₄2- had significant spatial and seasonal variation at p<0.04 and p<0.002, respectively. Cadmium, Pb, and PO₄3˗ exceeded the NESREA permissible limits for surface water (0.003, 0.01 and 3.5 mg/L, respectively). Turbidity correlated significantly with Fe (r=0.6) and SO₄2- (r=0.7). The PCA revealed high positive loading for water temperature (0.7 °C), hardness (0.6 mg/L CaCO3) and turbidity (0.6 FTU). Forty-five species of phytoplankton belonging to four Classes: Bacillariophyceae (25 species), Chlorophyceae (Nine species), Euglenophyceae (Eight species) and Cyanophyceae (Three species) were recorded. Merismopedia punctata (52.1%) dominated the phytoplankton population. Zooplankton from three groups: rotifers (15 species), crustaceans (five species) and insects (one species) were encountered. Mesocyclops leuckarti (11.6%) was the most abundant zooplankton. Diversity index for phytoplankton was highest in station iv; stations ii and iii recorded highest HI for zooplankton. Eight species of macrozoobenthos were recorded with the gastropod, Indoplanorbis exustus (30.9%) dominating and the insect, Chironomus species (11.8%) was the least abundant. Twenty-four fish species were recorded. Family Cichlidae (22.6%) was the most abundant. Pollution indicator species were abundant and included the phytoplankton, Merismopedia punctata (52.1%) and the macrozoobenthos, Melanoides tuberculata (24.7%). This study provided baseline information on the ecological status of Ibuya River. However, the composition and diversity of both plankton and macrozoobenthos could be potentially used as bio-indicators for assessing and monitoring Ibuya River.